Treatment of renal angiomyolipoma: pooled analysis of individual patient data. Issue 1 (December 2015) - Kuusk, Teele; Biancari, Fausto; Lane, Brian; Tobert, Conrad; Campbell, Steven; Rimon, Uri; D'Andrea, Vito; Mehik, Aare; Vaarala, Markku
Abstract Background This study was performed to evaluate the impact of baseline characteristics and treatment methods on the outcome of sporadic renal angiomyolipoma (AML). Methods This was a pooled analysis of individual data of 441 patients with AML retrieved from 58 studies and 3 institutional series. Results Ninety-three patients underwent nephrectomy, 163 partial nephrectomy/enucleation, 128 embolisation, 19 cryoablation, 6 radiofrequency ablation, and 32 conservative treatment. Their mean follow-up period was 44.5 months. Patients who experienced major bleeding at presentation had significantly larger tumours than did those without bleeding (mean diameter, 10.1 vs. 5.9 cm, respectively;p <  0.0001). A total of 9.4 % and 26.4 % of bleeding tumours had a diameter of <4 and <6 cm, respectively. A tumour diameter of ≥8.0 cm (hazard ratio, 2.07; 95 % confidence interval, 1.20–4.77) and the treatment method (p =  0.001) were independent predictors of re-intervention. The risk of re-intervention was significantly higher after embolisation, particularly for large tumours (5-year rate of freedom from re-intervention: diameter of ≥8.0 cm, 49.2 %; diameter of <8.0 cm, 74.8 %;p =  0.018). Conservatively treated AMLs had a mean baseline diameter of 3.2 ± 2.7 cm; after 41 months, their mean diameter was 3.7 ± 3.1 cm (p =  0.109). Conclusions The prevalence of major bleeding is high in sporadic AMLs with a diameter of >6 cm. These results suggest that conservative treatment can be considered in AMLs of <6 cm in diameter. Among current treatment methods, embolisation was associated with a significantly higher risk of re-intervention. Further studies are needed to define risk factors for bleeding and assess the relative benefits of different treatment modalities.